Curriculum Integration in Islamic Boarding School: A Case Study of Al-Ihsan Boarding School, Riau - Rini Setyaningsih; Muhammad Aryo Ramadhan; Merrina Ulfa; Siti Anne Barkah Nur Fauziah (Nadwa: Jurnal Pendidikan Islam, 2025)
The increasing demand for Islamic boarding schools to deliver both religious and academic education has prompted curriculum integration efforts nationwide. However, previous studies have not fully addressed how pesantren practically implement this integration while maintaining educational quality. This study explores how Al-Ihsan Boarding School in Riau integrates the Diniyah Curriculum with the National Curriculum, focusing on implementation practices, challenges, and institutional responses. The main research problem centers on how pesantren can balance two different pedagogical frameworks within a limited time and capacity. Using a qualitative approach with descriptive analysis, data were collected through in-depth interviews and observations involving the Deputy Head of Curriculum and the Boarding School Leader. The data were analyzed thematically through stages of data condensation, categorization, interpretation, and verification. Findings reveal that integration enhances students’ competencies across both curriculum domains, yet faces challenges including contrasting instructional methods, time constraints, and varied student preparedness. To overcome these, Al-Ihsan has developed contextualized support strategies, such as study clubs and tutoring sessions, which help students adapt and succeed. This study contributes a context-specific model for curriculum integration in pesantren and recommends future research on broader institutional comparisons, as well as policy support for adaptive academic management in Islamic boarding schools.